Online reviews on E-commerce platforms in Vietnam: The role of trust in behavioral intention - Phuong Duy, Nguyen Binh; Kien, Dang Trung; Thinh, Vuong Minh; Phuong Thuy, Nguyen Binh (International Journal of Informatics and Communication Technology (IJ-ICT), 2025)
This comprehensive study thoroughly explores the factors related to online reviews that influence users’ purchase intention through trust. Drawing on robust theoretical foundations and relevant research, the study establishes connections between trust-promoting factors and user behavioral intentions on e-commerce platforms in Vietnam. The study, which involved a survey of 680 users for data collection and partial least squares structural equation modeling (PLS-SEM) analysis, unveils that the usefulness of online reviews is the key driver of behavioral intention. Moreover, trust plays a pivotal mediating role in linking the quality and rating of online reviews to users’ purchase intentions. These findings not only enrich the theoretical foundation of behavioral research on online platforms but also offer practical managerial implications, empowering e-commerce platforms to develop a comprehensive review system and enhancing users’ online shopping experience.